ANALISIS FAKTOR PENGHAMBAT PENERAPAN SISTEM MANAJEMEN K3 SERTA LANGKAH MENCIPTAKAN SAFETY CULTURE TERHADAP PT. GUNANUSA UTAMA FABRICATORS - Khurin Putri; Fuad Mahfud Assidiq (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2022)
Occupational Safety and Health (K3) is very important for companies that have a high risk of work accidents, especially companies related to construction work. The implementation of the OHS program that has been made by the company with an OHS culture that has become a habit of every worker, is expected to be able to improve the performance of construction projects. The Occupational Safety and Health Management System is one of the most important factors, but in its implementation there are many inhibiting factors and work risks. Effective implementation of OHS can reduce the occurrence of work accidents. However, in reality on construction projects, the implementation of OHS is often hampered. Factors causing the low implementation of the Occupational Safety and Health Management System (OHSMS) in construction companies such as fulfillment of laws and regulations, commitment to OHS policies, people and the environment as well as budget and finance. In addition, safety culture is a product of individual or group values, attitudes, perceptions, competencies, and patterns of behavior that show commitment and implementation of OHS. Today, many large companies have implemented or are implementing safety culture in order to maintain the continuity of the production process.